Studi Tentang Brand Awareness pada Bodycare Halal di Social Commerce dan Dampaknya terhadap Purchase Intention - Anastasia Anggi Fernanda; Usep Suhud; Daru Putri Kusumaningtyas (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This study aims to determine the effect of brand awareness, brand image, electronic word of mouth (e-WOM), and brand trust on purchase intention on halal bodycare in social commerce TikTok. The method used in this study is quantitative through a questionnaire with a six-point Likert scale. This study uses SEM (Structural Equation Model) AMOS and SPSS in processing data with 252 respondent samples. The characteristics of the sample for this study are people who live in the Jakarta area, have an interest in buying halal bodycare products and are over or equal to 17 years old. The results of the study show that brand awareness has a positive and significant effect on brand image, brand awareness has a positive and significant effect on e-WOM, brand awareness has a positive and significant effect on brand trust, brand image has a positive and significant effect on purchase intention, e-WOM has no effect on purchase intention, and brand trust has a positive and significant effect on purchase intention.